2016
DOI: 10.1074/jbc.m116.750463
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Recognition of the Cancer Glycobiomarker, LacdiNAc (GalNAc[β1→4]GlcNAc), by Wisteria floribunda Agglutinin

Abstract: Neoplastic transformation often results in cells with unusual glycosylation patterns specific to the type and stage of different cancers, providing numerous venues for therapeutic and diagnostic reagents (1, 2). Lectins are non-catalytic proteins with strict specificity for individual mono-or oligosaccharides, which can make them powerful tools for detecting changes in the carbohydrate structure in glycoproteins and glycolipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 62 publications
4
41
0
Order By: Relevance
“…PSA from seminal plasma of healthy men and LNCaP-conditioned medium were also simultaneously analysed using the same set of lectin columns. Several reports have shown that the LacdiNAc structure is abundantly expressed in LNCaP cancer cell and this was examined as the cancer-related glycomarker 14,15 ; we measured the amount of PSA with LacdiNAc using Wisteria floribunda agglutinin (WFA) column chromatography. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PSA from seminal plasma of healthy men and LNCaP-conditioned medium were also simultaneously analysed using the same set of lectin columns. Several reports have shown that the LacdiNAc structure is abundantly expressed in LNCaP cancer cell and this was examined as the cancer-related glycomarker 14,15 ; we measured the amount of PSA with LacdiNAc using Wisteria floribunda agglutinin (WFA) column chromatography. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…WFA has been used as a tool for revealing areal borders and subdivisions. As LacdiNAc (β- d -GalNAc-[1→4]- d -GlcNAc) is associated with tumor malignancy in leukemia, prostate, pancreatic, ovarian, and liver cancers, WFA is promising for cancer glycobiomarker detection [ 10 , 39 ]. rD2BPL3 recognizes LacdiNAc, similarly to WFA; thus, rD2BPL3 is strong candidate for the development of a cancer glycobiomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Gal/GalNAc-specific lectin is a vaccine candidate for amoebiasis and a focus of immunogenicity studies [ 9 ]. Wisteria floribunda agglutinin (WFA), a GalNAc-specific lectin, shows promise for cancer biomarker detection, with disaccharide LacdiNAc (β- d -GalNAc-[1→4]- d -GlcNAc) recognition properties [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though β-galactosides are generally recognized as Gal-3 ligands, we recently found that the terminal N , N′ -diacetyllactosamine (LacdiNAc; GalNAcβ1,4GlcNAc) epitope acts as a selective ligand of Gal-3 compared to galectin-1 [ 6 , 7 ]. The LacdiNAc disaccharide specifically occurs in some O - and N -linked mammalian glycoproteins and has specialized functions [ 8 , 9 ]; it has also been identified as a specific glyco-biomarker in several types of cancers [ 10 , 11 , 12 ]. Otherwise, it is overexpressed in parasites [ 13 ] and other organisms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%